Veterinary Cuttable Plate in a Plate-Rod Construct for Repair of Diaphyseal Femoral Fractures in the Cat - Vedrine, Bertrand; Gérard, Fabien (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This study evaluated retrospectively the effectiveness of the veterinary cuttable plate (VCP) in a plate-rod construct, for the treatment of diaphyseal femoral fractures in cats.Materials and Methods A total of 29 cats with diaphyseal femoral fracture underwent stabilization with a VCP-rod construct.Results Fractures were classified as type A (7/29), type B (11/29) and type C (11/29) following the AO classification. Biological osteosynthesis was elected in three type B and 10 type C fractures, and open approach in the other cases. Pin diameter was 2 mm (n = 16) or 2.5 mm (n = 13); this corresponded to a percentage of pin occupation of 39.9 and 53.0% of the intramedullary cavity respectively. The 2.0/2.7-mm VCP and 2-mm screws were used in all cases. The median length of the VCP was 12 holes, and the median number of screws placed in the plate was 6. The median number of cortices engaged per fragment was 6. Ninety-nine percent of the screws were bicortical. Quadriceps contracture was an unacceptable functional outcome in one cat. Follow-up was available in 20 cases. Complete bone healing was assessed in 16/20 cases with a functional outcome considered as full in 17/20, acceptable in 2/20, and unacceptable in 1/20. Telephonic owner outcome assessment was available for five more cats and was considered as full in all cases.Clinical Significance The VCP-rod construct is effective to manage all configurations of diaphyseal femoral fracture in cats. The high amount of screw holes per unit length of a VCP allows bicortical screws placement without interfering with the intramedullary rod.
Keywords: veterinary cuttable plate; plate-rod; femur; cat; fracture